2017
DOI: 10.1051/matecconf/201711700108
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the dynamic behavior of railway track taking into account the occurrence of defects in the system wheel-rail

Abstract: Abstract. This paper investigates the influence of wheel defects on the development of rail defects up to a state where rail prompt replacement becomes necessary taking into account different models of the dynamic contact between a wheel and a rail. In particular, the quasistatic Hertz model, the linear elastic model and the elastoplastic Aleksandrov-Kadomtsev model. Based on the model of the wheel-rail contact the maximum stresses are determined which take place in the rail in the presence of wheel defects (e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Despite all efforts on increase in level of safety when transporting freights and passengers, the number of accidents and descents on railway transport doesn't decrease [3]. The main reason for the majority of freight train crashes is the growth of highly defective stages, which depends on many factors, including high-frequency vibrations which arise from micro-breaks of wheels from the railway [4,5,13]. The occurrence of high-frequency vibrations in the elements of the rolling stock and the railway is probably when the transport passes through artificial structures, for example bridges constructed according to various design schemes: made of reinforced concrete or steel (refer with: Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite all efforts on increase in level of safety when transporting freights and passengers, the number of accidents and descents on railway transport doesn't decrease [3]. The main reason for the majority of freight train crashes is the growth of highly defective stages, which depends on many factors, including high-frequency vibrations which arise from micro-breaks of wheels from the railway [4,5,13]. The occurrence of high-frequency vibrations in the elements of the rolling stock and the railway is probably when the transport passes through artificial structures, for example bridges constructed according to various design schemes: made of reinforced concrete or steel (refer with: Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In the works [1,2,5] is shown that with high-frequency vibrations arising in the vehiclerailway system the mechanisms of destruction are different than at low frequencies [6-8, 10, 11]. As practical operating a rail-sleeper lattice on bridge crossings shows [14,20,[21][22][23], may be emergence rail defects that can go to the highly defective stages and lead to a catastrophe or (in case of timely detection) to the closure of traffic. These include: code defects 30G.2 -longitudinal cracks in the transition zone of the head to the web (refer with: Fig.…”
Section: Introductionmentioning
confidence: 99%